Parental Involvement In Shaping Children’s Religious Character: A Qualitative Study At Madin Al Istiqomah - Hartatik, Wahyu Sri; Wulandari, Dea Rakhimafa (Jurnal Penelitian, 2025)
This study examines the role of parents in shaping the religious character of children aged 7 to 12 at Madin Al Istiqomah. The research aims to identify and evaluate the influence of parents on children’s character development. A descriptive qualitative approach was utilized, with data collected through interviews, observations, and document analysis. Findings reveal that parents act as primary introducers of religious values through strategies such as role modeling, habituation of worship practices, and utilizing leisure time for positive activities. The madrasah diniyah complements this role by providing spiritual programs, and collaboration between parents and the institution fosters a supportive environment for children’s religious growth despite challenges from environmental factors and social media. This study contributes to the literature on family-based religious education and offers practical guidance for parents and educators on enhancing children’s moral and spiritual development.